Web-Based Cash and Drug Inventory Information System Implementation Model at Ayah Bunda Pharmacy - Tia Oktavia; Erliany Syaodih; Ign. Wiseto P. Agung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Manual and semi-digital cash and medicine-recording processes in community pharmacies create risks of delayed reporting, duplicated entries, stock discrepancies, and weak managerial control. This study examined the implementation of a web-based cash and drug inventory information system at Ayah Bunda Pharmacy, Binjai, North Sumatra, by integrating the DeLone and McLean Information Systems Success Model with a Content Management System perspective. A qualitative case-study design was applied. Data were collected through semi-structured interviews, direct observation, and documentation involving the pharmacy owner, administrative personnel, cashiers, and pharmacy staff. Data were analyzed using the interactive model of reduction, display, and conclusion drawing. The findings indicate that the system provided accessible navigation, adequate speed and stability, integrated transaction and inventory data, responsive technical support, role-based access, and flexible content updating. Information quality was strong for cash and reporting functions but remained dependent on disciplined and complete stock input. Use intensity differed across functions: pharmacy staff used the system routinely, while some cashiers remained in transition from manual routines. Overall, the system improved reporting efficiency, stock visibility, transparency, and data-based decision making. The proposed implementation model emphasizes system integration, user discipline, technical readiness, continuous training, and governance controls as mutually reinforcing conditions for sustainable pharmacy digitalization.